Building Green Hotel Image Through Employee's Green Behaviour in Five Star Hotel in Bali - Astawa, I Ketut; Budarma, I Ketut; Widhari, Cokorda Istri Sri; Suardani, Anak Agung Putri (Technium Social Sciences Journal, 2021)
This study investigates the effect of hotel employees' green awareness, knowledge, and skill on their intention to implement green practices in a 5-star hotel in Bali. The study is guided by the hotels' green ability model with data collected through a survey from 82 hotel operational staff, supervisors, middle and top managers of 5-star hotels in Bali. Furthermore, the research hypothesis of the data obtained was analyzed using SEM-PLS 3.3.3. The result showed that employees’ environmental knowledge and awareness contribute significantly to their intention to implement green practices, while their green skill is weakly influenced. Additionally, employees' intention to implement green practices positively affects green hotel image. Therefore, this research also discussed the theoretical and practical implications.